PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Kirana, Arinta Rara (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The problems studied in this study are related to the low ability of students to solve mathematical problems. The purpose of this study was to determine the effect of the Blended learning model on the mathematics problem solving ability of grade VIII students of even semester SMP Negeri 34 Bandar Lampung for the 2019/2020 academic year. This study used an experimental method with the population in this study, namely all students of class VIII even semester of SMP Negeri 34 Bandar Lampung which consisted of eight classes with a total of 238 students, while the sample was taken from two classes, namely class VIII-A as an experimental class that applied the Blended learning model. and class VIII-B as a control class that applies conventional learning models. Samples were taken using cluster random sampling technique. To find out the students' ability to solve mathematical problems, the writer conducted a test in the form of an essay of five questions which had been tested for validity and reliability first. Hypothesis testing in this study uses the t-hit formula. From the results of hypothesis testing using the t-hit statistical formula, the value of = 3.14 is obtained. From the t distribution table at a significant level of 5%, it is known that = 1.68, then >, which means that the average mathematical problem solving ability of students who use the Blended learning model is higher than the average mathematical problem solving ability of students who use the learning model conventional.